Hydroxyapatite-Coated SPIONs and Their Influence on Cytokine Release - Friedrich, Bernhard; Auger, Jean-Philippe; Dutz, Silvio; Cicha, Iwona; Schreiber, Eveline; Band, Julia; Boccaccini, Aldo R.; Krönke, Gerhard; Alexiou, Christoph; Tietze, Rainer (International Journal of Molecular Sciences, 2021)
Hydroxyapatite- or calcium phosphate-coated iron oxide nanoparticles have a high potential for use in many biomedical applications. In this study, a co-precipitation method for the synthesis of hydroxyapatite-coated nanoparticles (SPIONHAp), was used. The produced nanoparticles have been characterized by dynamic light scattering, X-ray diffraction, vibrating sample magnetometry, Fourier transform infrared spectrometry, atomic emission spectroscopy, scanning electron microscopy, transmission electron microscopy, selected area diffraction, and energy-dispersive X-ray spectroscopy. The results showed a successful synthesis of 190 nm sized particles and their stable coating, resulting in SPIONHAp. Potential cytotoxic effects of SPIONHAp on EL4, THP-1, and Jurkat cells were tested, showing only a minor effect on cell viability at the highest tested concentration (400 mu g Fe/mL). The results further showed that hydroxyapatite-coated SPIONs can induce minor TNF-alpha and IL-6 release by murine macrophages at a concentration of 100 mu g Fe/mL. To investigate if and how such particles interact with other substances that modulate the immune response, SPIONHAp-treated macrophages were incubated with LPS (lipopolysaccharides) and dexamethasone. We found that cytokine release in response to these potent pro- and anti-inflammatory agents was modulated in the presence of SPIONHAp. Knowledge of this behavior is important for the management of inflammatory processes following in vivo applications of this type of SPIONs.
CRIS-Team WoS Importer:2021-05-14